2007
DOI: 10.2169/internalmedicine.46.6237
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia Gravis and Diabetes Mellitus: -A 35-year Retrospective Study-

Abstract: Myasthenic patients with diabetes mellitus could be classified into 2 groups, one group with positive organ-specific autoantibodies to many organs (with type 1 diabetes mellitus), and the other group with diabetes mellitus onset during prednisolone administration (with type 2 diabetes mellitus).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
4
8
0
Order By: Relevance
“…The gender prevalence of DM was higher in men in the general population (17) and patients with MG (4) and RA (12). Our MG cohort study confirmed these results, which is atypical compared with the higher MG prevalence in female patients (4,16).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The gender prevalence of DM was higher in men in the general population (17) and patients with MG (4) and RA (12). Our MG cohort study confirmed these results, which is atypical compared with the higher MG prevalence in female patients (4,16).…”
Section: Discussionsupporting
confidence: 77%
“…This nationwide population-based cohort study demonstrated that MG was associated with risk of DM in 1520 Taiwanese patients with MG. The prevalence of DM in MG patients has varied widely from 2% to 16.7% in previous hospital-based reports (4,5,11). This variability might be related to the selection criteria of DM and the length of observation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is more frequent in men than women (29 vs 16 %). Patients with MG and DM may have positive more organ-specific antibodies (with DM type 1), or onset of DM during corticosteroid therapy (DM type 2) [ 38 ]. Doses of prednisolone higher than 30 mg/day increase the level of glycaemia in patients who already have DM, and can cause glucose intolerance or diabetes in previously normoglycaemic subjects [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among refractory MG patients, 22 patients (28.94%) have diabetes mellitus. Detailed prevalence reports of association of diabetes mellitus with MG are lacking, but it is estimated to be 2–3% [ 32 ], [ 33 ]. According to a Taiwanese study, MG cohort had a 1.26-fold increased risk of developing DM compared with the comparison cohort [ 34 ].…”
Section: Discussionmentioning
confidence: 99%